Adaptation Amidst the Threat of Land Subsidence: The Role of Living Comfort for the Coastal Communities of Semarang - Damai Sinar Pertiwi; Juhadi Juhadi (Universitas Lambung Mangkurat, 2025)
The city of Semarang has experienced rapid growth recently, particularly in the industrial and transportation sectors. This development has led to an increased demand for land, especially in coastal areas, which has in turn triggered the conversion of ponds and swamps into industrial and residential areas. Many newcomers also choose coastal areas as their residential locations, although these are often developed without adequate spatial planning. This situation accelerates land subsidence, which directly impacts the lives of surrounding communities. In this context, the community's ability to adapt becomes crucial. One factor influencing this adaptability is the level of residential comfort. This study aims to understand the relationship between residential comfort and community adaptation strategies to land subsidence in Terboyo Kulon Village. Through a survey of 30 respondents and data collection via questionnaires, interviews, observations, and document studies, the research found that the community applies three main forms of adaptation: protective adaptation, accommodative adaptation, and retreat adaptation. These three forms of adaptation have a positive relationship with perceptions of residential comfort. These findings suggest that improving residential comfort can strengthen community resilience in the face of environmental changes such as land subsidence.